A Case Study to Address the AACSB Curricula Management Review - McCarthy, Mary; McCarthy, Mary; McCarthy, Richard; Bell, Timothy J; Bell, Timothy J (Archives of Business Research, 2017)
This paper examines a curricula management improvement process model to apply to the review of a business school core curriculum consistent with AACSB (Association to Advance Collegiate Schools of Business International) Standard 8. AACSB accredited schools are required to perform periodic curricula management review. A flexible business process model extensible to other curriculum programs is proposed. The results of the model implementation from an action-research study at a medium-size public university in the northeastern United States are discussed. AACSB requires that a continuous improvement review process for curricula management be in place. However, there is a lack of formal business processes to address how business schools can systematically manage their curriculum. This paper bridges that gap by presenting a formal approach. Lessons learned from the process and recommendations are also presented.